2019
DOI: 10.30970/sbi.1301.591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of novel 2-amino-5-benzylthiazole derivative on cellular ultrastructure and activity of antioxidant system in murine lymphoma cells

Abstract: 10 and 50 µM activate superoxide dismutase and lead to a decrease of the activity of catalase and glutathione peroxidase. This effect suggests that the change in the activity of enzymes leads to accumulation of H 2 O 2 in the lymphoma cells. Such results indicate that the studied substance can realize its cytotoxic effect through the action of the antioxidant system. The obtained data can be used to carry out further preclinical studies of the thiazole derivatives as potential antitumor drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…The action of the substance led to a deformation of the plasma membrane and nucleus, and to a decrease in the nucleus/ cytoplasmic ratio. These changes are similar to the effect of thiasole derivative (PP2) when lymphoma cells were incubated with the chemical in vitro [14]. We believe that these morphological changes are the result of apoptosis-like perturbations, such as an activation of poly (ADP-ribose) polymerase 1 and caspase 3 cleavage, as well as an increase in the level of pro-apoptotic Bim protein and the mitochondrion-specific EndoG nuclease, and a decrease in the level of the anti-apoptotic Bcl-2 protein [3].…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…The action of the substance led to a deformation of the plasma membrane and nucleus, and to a decrease in the nucleus/ cytoplasmic ratio. These changes are similar to the effect of thiasole derivative (PP2) when lymphoma cells were incubated with the chemical in vitro [14]. We believe that these morphological changes are the result of apoptosis-like perturbations, such as an activation of poly (ADP-ribose) polymerase 1 and caspase 3 cleavage, as well as an increase in the level of pro-apoptotic Bim protein and the mitochondrion-specific EndoG nuclease, and a decrease in the level of the anti-apoptotic Bcl-2 protein [3].…”
Section: Resultssupporting
confidence: 59%
“…PP2 complexed with polymeric carriers at concentration of 10 µM caused changes of apoptotic type in the ultrastructure of lymphoma cells. Earlier, it was shown that 2-amino-5-benzylthiazole derivative caused necrosis in lymphoma cells in vitro [14]. In this study, necrotic changes in the ultrastructure under the action of the studied substances were not observed, while signs of apoptotic changes were detected.…”
Section: Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…Mitochondria play an important role in cellular metabolism, including production of reactive oxygen species (ROS). It was shown that the studied compounds activate superoxide dismutase and decrease the activity of catalase and glutathione peroxidase doi: https://doi.org/10.15407/ubj92.02.121 [9]. These effects may lead to accumulation of H 2 O 2 in lymphoma cells, which can be toxic for cancer cells.…”
mentioning
confidence: 99%